Information needs research in Russia and Lithuania, 1965-2003 - Elena Maceviciute (Information Research: An International Electronic Journal)
Introduction. /strong>. The invisibility of research on information needs from the East and Central Europe in the West suggested an exploration of the published research output from Lithuania and Russia from 1965 to 2003. Method. The data were collected from the abstracting journal Informatika-59. The publications were retrieved from Lithuanian and Russian libraries or the Internet. Analysis. The texts and, in cases when full-texts were not available, the abstracts were used for qualitative analysis assessing the relevance, content, concepts used and their change over time. Comparison with the Western (English language or Anglo-American) literature was carried out. Results. /strong>. The development of the concept of information user needs in Russia and Lithuania is followed through several decades as well as the understanding of its origins, structure and typologies. The parallel concepts and similar ideas are traced in the Western information behaviour literature. A context of related research (reading studies and information literacy) is revealed. Conclusion. . Despite the isolation of two bodies of research (Western and East European) in the area of information needs the common development and similarities in the understanding of the basic concept of information need, its origin and structure as well as typologies are revealed. Basic differences lie in understanding the contexts of the formation of information needs, their influence and, consequently, attention to the roles of contexts in research. It also seems that the everyday, non-work related information needs are totally excluded from the horizons of Russian researchers.